Побудова множини критеріїв оптимізації укладання розкладу навчальних занять у ВЗО - Верес, О. М. (Видавництво Національного університету “Львівська політехніка”, 2020)
Such terms as “disition”, “purpose”, ’’criteria”, “indicators” are described in this article. Grounded set of criteria optimisation arangement of estabîishirig the studing process scheduling.
Keywords: 681.3